THE SERVICE QUALITY AND PRICE IMPACT ON CUSTOMER SATISFACTION AND LOYALTY ON PT. ADIRA FINANCE SIMPANG EMPAT - Erdawati, Erdawati; Asraf, Asraf; Larasati, Widia (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThe financial company's marketing program is aimed at maximizing customer satisfaction and loyalty. PT. Adira Finance Simpang Empat Branch is very aware of this, so various efforts have been made to build customer satisfaction and loyalty, including through improving service quality and competitive prices. This research was conducted to see the effect of service quality and price on customer satisfaction and loyalty. When this research was done, there were 6,207 existing customers and 98 of them were sampled through calculations using the Slovin formula. The results showed that service quality and price both partially and simultaneously had a significant effect on customer satisfaction and loyalty. Meanwhile the satisfaction variable also mediates the effect of service quality and price on loyalty. The implication of the results of this study is that in order to maintain and increase customer satisfaction and loyalty, PT. Adira Finance Simpang Empat can continue and improve its service quality and competitive pricing strategy.Keywords: Service Quality, Price, Customer Loyalty and Customer Satisfaction